INTERMEDIATE MODEL FOR FLUID FILTRATION IN MULTI-LAYERED OIL FIELDS - Tuhtanazarov Dilmurod Solijonovich (Web of Journals Publishing, 2023)
The motion of gas and oil to the chinks in the layer is very complicated. When the layer is multilayered, the process becomes even more complex. For the research of such tasks, certain number of works were dedicated and studied.